Characterization of Biofilm production in antibiotic resistant Klebsiella pneumonia isolated from different clinical samples in Iraqi hospitals - Rawa Abdul Redha Aziz; Sawsan Sajid Al-Jubori (Journal of Global Pharma Technology, 2017)
Objective(s): Klebsiella pneumonia is a causative agent of chronic infections leading to increase morbidity and mortality; especially when performing biofilm(1). Therefore, biofilm formation has been linked to the survival of pathogenic bacteria in the hospital environment, leading to susceptible bacterial colonization which creates an important public health problem. Therefore, to characterize biofilm production in local Iraqi K. pneumonia isolated from different clinical samples in Iraqi hospitals using phenotypic biofilm assays including scanning electron microscopy. Material and Methods local isolates were collected from different Iraqi hospitals and re-diagnosed by compact Vitek 2 and genetically by using housekeeping gene (16s rRNA and 23s rRNA 639 bp). Phenotypic detection of biofilm formation among isolates was screened by using microtiter dish assay, twitching motility assay, and scanning electron microscopy (SEM).Results: It was found that 22/24 (91.67%) of isolates could form biofilm (OD≥0.68). Twitching motility test revealed that 20/24 (80.3%) of isolates could move on the M63 medium. Scanning electron microscopy showed 83.3% of K. pneumoniae isolates made biofilm in different stages started with adhesion step and ending with a mushroom like architecture as highly magnification images showed on glass cover slips embedded statically in LB broth. It was interesting that K. pneumoniae S2 demonstrated a dense mat of cells aggregates on cover slips generating different biofilm formation step. Conclusion K. pneumonia could produce biofilm, describing the ability to resist many kinds of antibiotics and rising a concern of disseminating chronic infection among hospitalized patients in many hospitals in Baghdad.